Effects of different footwear on kinetics, kinematics and muscle forces during the barbell back squat; an exploration using Bayesian modelling. (1st September 2020) - Sinclair, Jonathan; Butters, Bobbie; Taylor, Paul John; Stone, Mark; Bentley, Ian; Edmundson, Christopher James
Abstract: The current study aimed to explore the effects of different footwear on kinetics, kinematics and muscle forces during the barbell back squat in both male and female lifters using Bayesian modelling. Twelve male and twelve female lifters completed squats at 70% of their 1 repetition maximum, in four different footwear conditions (Adidas weightlifting shoe, Inov-8 weightlifting shoe, Cross-fit and minimal footwear). Three-dimensional kinematics were measured using an eight-camera motion analysis system, ground reaction forces using a force platform and muscle/joint forces using musculoskeletal modelling techniques. Differences between footwear were examined using Bayesian 4 (FOOTWEAR) * 2 (GENDER) mixed ANOVA's. Peak quadriceps force was greater in the Adidas (male = 89.78/female = 70.56 N/kg), Cross-fit (male = 92.41/female = 70.82 N/kg) and Inov-8 (male = 91.57/female = 68.21 N/kg) conditions compared to minimal footwear (male = 82.61/female = 64.40 N/kg). In addition, peak patellofemoral stress and patellar tendon forces were greater in the Adidas (patellar tendon force: male = 64.67/female = 42.89 N/kg & patellofemoral stress: male = 143.21/female = 118.92 KPa/kg), Cross-fit (patellar tendon force: male = 67.89/female = 43.52 N/kg & patellofemoral stress: male = 146.02/female = 114.73 KPa/kg) and Inov-8 (patellar tendon force: male = 64.08/female = 41.04 N/kg & patellofemoral stress: male = 193.09/female = 169.09 KPa/kg) conditions compared to minimal footwear (patellar tendon force: male = 56.75/female = 39.92 N/kg & patellofemoral stress: male = 134.06/female = 108.91 KPa/kg). Finally, angular ROM was greater in the minimal footwear (male = 28.04/female = 33.75°) compared to the Adidas (male = 26.85/female = 30.73°) and Inov-8 (male = 26.92/female = 32.63°) conditions. The findings from the current investigation therefore indicate that weightlifting footwear may be able to enhance lower extremity muscle development and improve squat biomechanics owing to a reduced trunk angular ROM; however, this is likely to be at the expense of increased knee joint loading.